URGENSI LABELISASI HALAL DI TINGKAT LOKAL - Dahlan Tamrin, Sudirman (El-QUDWAH, 2006)
Muslims are suggested to consume halal foods. Numerous statements show this obligation as written in the Qur’an and Hadis. However, not all products sold in markets or shops provide particular information about their status, whether halal or haram. The manufactories usually just mention briefly the contents of products in outer-parts of packages. To reduce the anxiety of Muslims, the idea of product labeling should be taken into account. It may help people choose their consumption by observing the halal labels printed out in packages. In the case of Malang where Muslims become the majority, the need of halal labeling seems difficult to be delayed. Hence, this research aims at measuring the urgency of halal labeling by interviewing several people from various backgrounds in order to map their concepts objectively.